FAKTOR PREDISPOSISI YANG MEMPENGARUHI PERILAKU IBU DALAM PEMBERIAN MAKANAN PENDAMPING ASI DINI - Sucianingsih, Herlina; Rahmayanti, Devi; Damayanti, Emmelia Astika F. (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
The factors that influence of early giving food complementary of breast milk consist ofpredisposing factors, supporting factors and driving factors. Predisposing factors consist of age,education, occupation, knowledge and attitude. The purpose of this research was to know analyzepredisposing factors influencing mother's in early giving food complementary of breast milk.Descriptive correlation research used cross sectional design. Sampling used purposive samplingtechnique amounted to 65 people. The results showed that most respondents were 20-35 years ofage, primary education, unemployment, good knowledge, positive attitude and many respondentsgave early breastfeeding. The result of the analysis showed that there was a correlation betweeneducation predisposing factor (p = 0.000) and knowledge level (p=0.046) that influenced motherbehavior in early breastfeeding and no correlation between age predisposing factor (p=0.155),job (p=0,480) and attitudes (p=0.569) affecting mother's behavior in early breastfeeding. It wasadvisable to the community to provide support for exclusive breastfeeding so that MP-ASI wasgiven according to the age of the baby.